Vitamin D–binding protein and pancreatic cancer: a nested case-control study. Issue 6 (22nd April 2015) - Piper, Marina R; Freedman, D Michal; Robien, Kim; Kopp, William; Rager, Helen; Horst, Ronald L; Stolzenberg-Solomon, Rachael Z
ABSTRACT: Background: Vitamin D–binding protein (DBP) is the primary carrier of 25-hydroxyvitamin D [25(OH)D] in the circulation. One prospective study in male smokers found a protective association between DBP and pancreatic cancer, particularly among men with higher 25(OH)D concentrations. Objective: The objective was to examine the association between DBP and pancreatic cancer risk in an American population. Design: We conducted a nested case-control study in the Prostate, Lung, Colorectal, and Ovarian Cancer screening trial cohort of men and women aged 55–74 y at baseline. Between 1993 and 2010, 295 incident pancreatic adenocarcinoma cases were reported (follow-up to 15.1 y). Two controls ( n = 590) were matched to each case by age, race, sex, and month of blood draw. We calculated smoking- and diabetes-adjusted ORs and 95% CIs with the use of conditional logistic regression. Results: DBP concentration was not significantly associated with pancreatic cancer overall [highest (≥7149.4 nmol/L) vs. lowest (<3670.4 nmol/L) quintile; OR: 1.75; 95% CI: 0.91, 3.37; P -trend = 0.25]. For serum 25(OH)D compared with the referent (50 to <75 nmol/L), individuals in the highest group had a significantly higher risk (≥100 nmol/L; OR: 3.23; 95% CI: 1.24, 8.44), whereas those in the lowest group had no significant association (<25 nmol/L; OR: 2.50; 95% CI: 0.92, 6.81). Further adjustment for DBP did not alter this association. Conclusion: Our results do not support the hypothesis that serum DBP or 25(OH)D plays a protective role in pancreatic cancer. This trial was registered at clinicaltrials.gov as NCT00339495.